Vertex transitive maps on the Klein bottle - Šuch, Ondrej (Ars mathematica contemporanea, 2011)
We examine properties of groups associated with vertex transitive maps on the Klein bottle. As an application, we prove that all 4-line vertex transitive maps on the Klein bottle introduced by Babai admit a free vertex transitive action, but there others that do not.
Keywords: Klein bottle; Kleinova steklenica; po točkah tranzitivni zemljevidi; tapetna grupa; vertex-transitive map; wallpaper group